The Strategy of the Head of the Puskesmas in Increasing Work Engagement and Organizational Citizenship Behavior on Patient Satisfaction at the Ambon Market Health Center - Lestari, Indah Puspita; Sari, Wenny Permata (Formosa Journal of Multidisciplinary Research, 2024)
The purpose of this study is to empirically demonstrate the hypothesis that has been tested on all variables in this study. The sample in this study was 70 people, namely outpatients who sought treatment on January 04-06, 2024. The sample was obtained using saturated sampling technique. The research design used in this study is a quantitative descriptive approach, which is a study method that has clear objectives, approaches, subjects, samples, research work steps, and data sources. The data analysis technique used linear regression with SPSS for windows version 25. After conducting the research, the study results show that the value of R2 = 0.728 x 100% = 72.8%, which means that the high influence of the influence of work engagement and organizational citizenship behavior on patient satisfaction at the Ambon Market Health Center reaches 72.8% while the rest reaches 27.2%, this is influenced by other factors that are not discussed in this study. The contribution of this study is that the results of this study should inform the basis for reflection, support and ideas for the research purpose of improving the quality of services affecting coverage. of the number of outpatient visits year. The existence of a superior service process at the Ambon Market Health Center will bring its own satisfaction to patients. From the results of the hypothesis testing, researchers receive information that three hypotheses can be accepted. Therefore, it can be concluded that the majority of respondents said that the health services provided at the Pasar Ambon Health Center can be said to be very good.